Analisis Faktor Penyebab dan Dampak Tindak Pidana Pencurian Terhadap Pelaku Yang Mengidap Narkoba : Studi Kasus di Desa Paya Gambar - Soddik, M. Bahri Al; Fitri, Yuliza Anisa; Ahmad, Aldeo Nur; Herianto, Herianto; Rafly, M.; Atmadianti, Sri; Usiono, Usiono (Jurnal Ilmiah Wahana Pendidikan, 2024)
Drug abuse has a huge negative impact on adolescents. Apart from being harmful to health and mentality, it is also dangerous for many people. form of moral decay in society is the emergence of social evil. Many theories circulate in an attempt to solve the problem from various fields of science, which will eventually become obsolete for real problems that continue to evolve. This study used a qualitative approach. The data collection technique used in this study was field research. The observation method is a method that collects data by direct observation. For this reason, the author is interested in raising this problem with the title Analysis of the Causes and Impact of the Crime of Theft Against Drugs Affected Actors: A Case Study in Paya Village.